(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The essay deals with the withdrawal of life-sustaining treatment from an adult in permanent vegetative state or in a minimally conscious state, in the absence of a will expressed by the patient. The Italian l. n. 219/2017 has not changed matters, because it does not explain how, in this case, autonomy and human dignity can be properly safeguarded. Under a comparative point of view, the essay deals with the French and the English statutory framework governing the scrutiny of any decision to withdraw clinically assisted nutrition and hydration.